An Analytical Field Study of Muslim–Christian Coexistence in Al Husn City within the Irbid Governorate of Jordan - Zaid Khaled Al Zuriqat; Mohammad Abdullah Al Tawallbeh (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2025)
This study aims to explore the lived reality of religious coexistence between Muslims and Christians within the local community of Al Husn, analyzing its social, cultural, and religious dimensions. The research proceeds from the hypothesis that interfaith coexistence in Al Husn is not a transient phenomenon but the outcome of a long historical and cultural accumulation, reflecting deeply rooted patterns of interaction and mutual understanding. A descriptive analytical method was employed to examine the manifestations of Muslim–Christian coexistence within their social and cultural contexts, complemented by a historical approach tracing the evolution of interfaith relations across generations. Field data were collected through a social survey of 237 randomly selected residents of Al Husn Municipality (Irbid Governorate), ensuring balanced representation across religion, age, and gender, thus reflecting the area’s real social diversity. Results revealed that coexistence between Muslims and Christians in Al Husn is grounded in mutual respect, daily interaction, and shared participation across various spheres education, workplaces, and social occasions. Moreover, folk heritage and collective memory act as cultural and emotional bonds reinforcing this form of coexistence. Promoting interreligious coexistence requires integrating shared ethical and cultural values into educational curricula, organizing joint religious and cultural events, and fostering positive media narratives. It also entails encouraging youth led initiatives and interfaith dialogue that cultivate respect and empathy among the younger generations. Despite the overall positive model of coexistence, challenges remain chiefly, the lack of scientific documentation of interfaith relations, limited dialogue platforms, and the need for media engagement in consolidating social harmony.